The Context of Heidegger’s Philosophy of Technology: Cassirer, Jünger, Spengler - Mickevičius, Tomas Nemunas (Problemos, 2019)
[full article and abstract in Lithuanian; abstract in English] In this article the context of the formation of some important elements of Heidegger’s philosophy of technology is presented. The parallels between Heidegger’s and Ernst Cassirrer’s, Ernst Jünger’s and Oswald Spengler’s philosophical reflection on the process of industrialisation are discussed. While discussing the connections of their conceptions the development of characteristic Heideggerian articulation of industrialization process comes to the fore, as well as of some important themes of Heidegger’s philosophy of technology: planetary scope of modern technology’s reach and impact and the notion of technology as destiny of the West and modern humanity in general.